What little Kitten wants - Harper, Kathryn (Cambridge : Cambridge University Press, 2017)
Min wants to play with Little Kitten; can she find something Little Kitten likes? In Red Band, the sense of story starts to be developed. Illustrations continue to support understanding but readers also need to use decoding skills. Slightly longer texts with less repetition extend high-frequency word knowledge. Contains full teaching support including learning outcomes, curriculum links and follow-up activities.
Keywords: Children's - stories; Juvenile - works